Recovering the (Mis)Promises of Critical Pedagogies in Neoliberal Times: A Turn to Ethics - Azzarello, Louise (Journal of the Canadian Association for Curriculum Studies, 2020)
There are many renderings of critical pedagogy and at the core of each theory is a desire for the common good and a more just world. However, neoliberal logic is undermining the foundational promises of critical pedagogies. What happens when teachers, schooled in these theories—these promises—work in buildings that are hostile, indifferent or simply pay lip service to such theoretical goals? What happens when teachers realize, witness and participate in education as a force of ongoing colonial and systemic oppressions based on sex, gender, class and race (Battiste, 2005; Dion, 2010; Gaztambide-Fernández, 2011; Noroozi, 2017)? What happens to teachers’ (critical) pedagogical praxis when all hope of change seems impossible, when the inevitability of the way-things-are sucks all hope out of you? In an attempt to grapple with the “pervasive atmosphere of capitalist realism” (Fisher, 2009, p. 16) that infiltrates and impedes the educational, I position public education in Berlant’s (2011) notion of cruel optimism and question the (mis)promises of critical pedagogies. In doing so, I consider a turn to ethics to recover the “educational in education” (Di Paolantonio, 2016, p. 148). I make this move to think through how an ethics of responsibility to and for others might be fostered in schools given the compromised place of public education today.